Молекулярна кухня як інноваційна ресторанна технологія - Куниця, Катерина Вікторівна; Якименко-Терещенко, Наталія Василівна; Болюх, Ірина Олегівна (Причорноморський науково-дослідний інститут економіки та інновацій, 2024)
У статті розглянуто молекулярну кухню як інноваційну ресторанну технологію і науковий підхід до харчування, насамперед з погляду хімічного складу, властивостей та перетворень інгредієнта, що використовується при приготуванні страв. Основна ідея молекулярної кухні полягає у зміні фізико-хімічних властивостей інгредієнтів для досягнення нових смакових та текстурних відчуттів. До основних принципів та технік молекулярної кухні належать: сферифікація, гелеутворення, емульсифікація, ліофілізація, нітрогенізація. Молекулярна кухня дозволяє створити унікальні смакові комбінації та текстури, які неможливо досягти традиційними методами приготування. Страви, створені з використанням молекулярних технік, часто виглядають як витвори мистецтва, що робить їх візуально привабливими для гостей. Використання натуральних інгредієнтів та мінімальна термічна обробка дозволяє зберегти більше поживних речовин у стравах.

The article examines molecular cuisine as an innovative restaurant technology and a scientific approach to food, primarily from the point of view of the chemical composition, properties and transformations of the ingredients used in cooking. Molecular cuisine as an innovative direction in cooking that combines science and gastronomy to create unusual dishes using advanced technologies and methods. The main idea of molecular cuisine is to change the physical and chemical properties of ingredients to achieve new taste and texture sensations. The basic principles and techniques of molecular cuisine include: spherification (a technique in which a liquid is turned into balls resembling caviar; this is achieved due to the use of sodium and calcium alginate), gelation (involves the use of various gelling agents such as agar-agar or gelatin, to create gel structures), emulsification (the process of mixing two mutually insoluble liquids to create foam-type emulsions and air textures), lyophilization (the process of removing water from the product at low temperatures and under vacuum, which allows you to preserve the texture and taste of the ingredients), nitrogenation (the use of liquid nitrogen for instant freezing of products, which allows you to create unexpected textures and effects). Molecular cuisine allows you to create unique flavor combinations and textures that cannot be achieved with traditional cooking methods. Dishes created using molecular techniques often look like works of art, making them visually appealing to guests. The use of natural ingredients and minimal heat treatment allows you to preserve more nutrients in dishes. An important applied direction of molecular gastronomy is the study of the relationship between food, its sensory perception and increasing the degree of consumer satisfaction, which can create wide opportunities for improving nutrition and, therefore, people's health.. An important positive aspect of the application of molecular gastronomy is, of course, the popularization of food science and public education in terms of traditional ways of cooking, as well as innovative approaches to food processing.
Molecular cuisine as an innovative restaurant technology
Keywords: молекулярна кухня; молекулярна гастрономія; інновації; сферифікація; су-вид; екструзійне варіння; molecular cuisine; molecular gastronomy; innovations; spherification; sous vide; extrusion cooking